The twelve dogs of Christmas : [large type] a novel - Wiggs, Susan (Center Point Large Print, 2024)
"Brenda Malloy wants nothing to do with Christmas ever again. Last year, Brenda and her husband rushed their beloved dog Tim to the emergency vet on Christmas Eve. The good news: Tim survived after the vet cleared the obstruction -- a pair of women's lace undies. The bad news: the undies were not Brenda's. A year after the breakup, Brenda has put her life back together. She's trained for a marathon, is writing a children's novel, and she's found purpose and healing as a volunteer with a dog rescue organization in Houston, Texas. The rescue partners with a program in Avalon, New York -- a small, snowy town deep in the Catskills. Now Brenda is arranging the transport of rescued dogs from Houston to Avalon -- just in time for a merry Christmas with their forever families. Brenda's friends worry about her driving a van two thousand miles with twelve dogs in crates, but she shrugs off their concern. How hard can it be? She knows the way, and she's just looking to escape the Christmas overload for a while. But a blinding snowstorm, an escaped mutt, and a life-saving encounter with Adam Bellamy -- a single dad and paramedic -- means Brenda has to stay in Avalon longer than she planned. As she drops off each precious pup at their new homes, some of the comfort and joy of the season begins to creep up on Brenda despite her determination to avoid the holidays. Perhaps you can bring Christmas into your heart after all . . . if you have the right furry friends to guide the way."--